A Survey of Rounding Practices in Canadian Adult Intensive Care Units - Holodinsky, Jessalyn K. (PLoS One, 2015)
OBJECTIVE: To describe rounding practices in Canadian adult Intensive Care Units (ICU) and identify opportunities for improvement. DESIGN: Mixed methods design. Cross sectional survey of Canadian Adult ICUs (n = 180) with purposefully sampled follow-up interviews (n = 7). MEASUREMENTS AND MAIN RESULTS: Medical directors representing 111 ICUs (62%) participated in the survey. Rounding practices varied across ICUs with the majority reporting the use of interprofessional rounds (81%) that employed an open (94%) and collaborative (86%) approach, occurred at the patient’s bedside (82%), and started at a standard time (79%) and standard location (56%). Most participants reported that patients (83%) and family members (67%) were welcome to attend rounds. Approximately half of ICUs (48%) used tools to facilitate rounds. Interruptions during rounds were reported to be common (i.e., ≥1 interruption for ≥50% of patients) in 46% of ICUs. Four themes were identified from qualitative analysis of participant responses to open-ended survey questions and interviews: multidisciplinarity, patient and family involvement, factors influencing productivity, and teaching and learning. CONCLUSIONS: There is considerable variation in current rounding practices in Canadian medical/surgical ICUs. Opportunities exist to improve ICU rounds including ensuring the engagement of essential participants, clearly defining participant roles, establishing a standardized approach to the rounding process, minimizing interruptions, modifying the role of teaching, utilizing a structured rounding tool, and developing a metric for measuring rounding quality.